新加坡英汉双语者手部动作动词习得研究 = The acquisition of hand action verbs by English-Chinese bilinguals in Singapore - 王皓舒 Wang Haoshu (2014)
本研究是一项聚焦于具体语义场的、面向英汉双语者的词汇发展研究。在词汇量发展的层面，我们首先以手部动作动词为例，自行设计了一套面向三至五岁新加坡英汉双语儿童的词汇发展测量工具，而后基于五百名儿童的测量结果及其背景资料，建立了适用于语言背景不同的儿童的词汇发展常模，并据此评估了他们的双语词汇量发展。在词汇语义习得的层面，我们通过动作演示和视觉观察相结合的实验方法对比追踪英汉单、双语儿童、青少年及成人对“扔抛类”近义动词的语义习得轨迹。在充分考虑新加坡双语者特殊性的前提下，我们综合讨论了语言学因素（如：双语输入、语言变体、词汇语义构成等）和非语言学因素（如：家庭SES水平、认知及身体发展水平等）对其词汇量发展和词汇语义习得的影响。研究双语者对手部动作动词的习得，不仅要分析他们的动词使用及理解，还需要充分讨论各种影响因素之间的交互作用，唯有如此，我们才可能正确认识并解释双语者的词汇发展轨迹。 This is a study of domain-specific lexical development in English-Chinese bilinguals. Taking Hand Action Verbs as the sampling vocabulary, we firstly measured the English and Chinese vocabulary sizes of 500 bilingual Singaporean children with our self-designed parental report. Based on the measurement results, we established developmental norms for children from different backgrounds and obtained preliminary evaluations of their bilingual vocabulary development. By analyzing the data collected from a series of behavioral and perceptual experiments, we carefully described and compared the acquisition trajectories of near-synonymous Throwing Verbs by monolingual and bilingual children, adolescents, and adults. With a full consideration of the uniqueness of Singaporean bilinguals, we discussed both linguistic (e.g., language input, language varieties, lexical semantics, etc.) and non-linguistic factors (e.g., family SES, cognitive development, physical capability, etc.) that showed influences on their vocabulary development and acquisition of verbs semantics. The overall findings show that to understand the lexical development of hand action verbs in bilinguals we need to focus not only on the acquisition and production of the verbs but also on how other influencing factors interact with each other to shape the developmental trajectory.